(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
These days, Latin is taken as the common language in medical parts of the world. It may be a foreign language, but intermedical in its significance. Latin language is written, read and understood in most parts of the world. Because of this language, people of the world communicate and belong to the whole shares of the world. It is widely accepted that Latin has become the language of choice for many international scholarly journals. This article approach developing students attitudes towards the environment when teaching a foreign languages